a.) A = P+P*r*t for r

Does anyone else get r = (A/P-1)/t ?

b.) d = (sqrt(4*R^2-C^2))/2 for C

Does anyone else get C = sqrt((-2d)^2)/4)+R^2

c.) 1/f = 1/q+1/p for q

Does anyone else just get f^-1-p^-1=q^-1?

Printable View

- Nov 29th 2008, 11:48 AMZE2001Solve for the Identified Variable
a.) A = P+P*r*t for r

Does anyone else get r = (A/P-1)/t ?

b.) d = (sqrt(4*R^2-C^2))/2 for C

Does anyone else get C = sqrt((-2d)^2)/4)+R^2

c.) 1/f = 1/q+1/p for q

Does anyone else just get f^-1-p^-1=q^-1? - Nov 29th 2008, 01:47 PMmasters
a) Your answer is correct, but I would have done it this way. Less complex:

$\displaystyle A=P+Prt$

$\displaystyle A-P=Prt$

$\displaystyle r=\frac{A-P}{Pt}$

b) You lost me on this one.

$\displaystyle d=\frac{\sqrt{4R^2-C^2}}{2}$

$\displaystyle d^2=\frac{4R^2-C^2}{4}$

$\displaystyle 4d^2=4R^2-C^2$

$\displaystyle 4d^2-4R^2=-C^2$

$\displaystyle 4R^2-4d^2=C^2$

$\displaystyle C^2=4R^2-4d^2$

$\displaystyle C=\sqrt{4(R^2-d^2)}$

$\displaystyle C=2\sqrt{R^2-d^2}$

c) I don't see where you solved for**q**in your attempt.

$\displaystyle \frac{1}{f}=\frac{1}{q}+\frac{1}{p}$

Multiply through by the LCD of**fqp**

$\displaystyle qp=fp+fq$

$\displaystyle qp-fq=fp$

$\displaystyle q(p-f)=fp$

$\displaystyle q=\frac{fp}{p-f}$